Manajemen Kinerja dan Manajemen Talenta sebagai Instrumen Penguatan Kapasitas Organisasi di Era Digital - Maghfira Izzani Tuzahra; Alfiyyah Azhar; Lisa Aprillia; Pupung Purnamasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Changes in the business environment due to digitalization require organizations to be able to adapt quickly. In this context, performance management and talent management are two important elements in strengthening organizational capacity to remain competitive. This research aims to analyze the integrative role of performance management and talent management in improving organizational effectiveness and competitiveness in the digital era. The research method used is descriptive qualitative with a literature study approach and field observations in the service and technology sectors. The study results show that companies that implement adaptive performance management systems and systematic talent development strategies tend to have higher levels of innovation and employee retention. This research recommends the implementation of competency-based performance appraisal systems and talent management strategies that support continuous learning.